Risk assessment of bisphenol analogues towards mortality, heart rate and stress-mediated gene expression in cladocerans Moina micrura - Razak, Muhammad Raznisyafiq; Aris, Ahmad Zaharin; Yusoff, Fatimah Md; Yusof, Zetty Norhana Balia; Abidin, Aisamuddin Ardi Zainal; Kim, Sang Don; Kim, Kyoung Woong (Springer, 2022)
Bisphenol A (BPA) is a well-known endocrine-disrupting compound that causes several toxic effects on human and aquatic organisms. The restriction of BPA in several applications has increased the substituted toxic chemicals such as bisphenol F (BPF) and bisphenol S (BPS). A native tropical freshwater cladoceran, Moina micrura, was used as a bioindicator to assess the adverse effects of bisphenol analogues at molecular, organ, individual and population levels. Bisphenol analogues significantly upregulated the expressions of stress-related genes, which are the haemoglobin and glutathione S-transferase genes, but the sex determination genes such as doublesex and juvenile hormone analogue genes were not significantly different. The results show that bisphenol analogues affect the heart rate and mortality rate of M. micrura. The 48-h lethal concentration (LC50) values based on acute toxicity for BPA, BPF and BPS were 611.6 µg L−1, 632.0 µg L−1 and 819.1 µg L−1, respectively. The order of toxicity based on the LC50 and predictive non-effect concentration values were as follows: BPA > BPF > BPS. Furthermore, the incorporated method combining the responses throughout the organisation levels can comprehensively interpret the toxic effects of bisphenol analogues, thus providing further understanding of the toxicity mechanisms. Moreover, the output of this study produces a comprehensive ecotoxicity assessment, which provides insights for the legislators regarding exposure management and mitigation of bisphenol analogues in riverine ecosystems.